Customers' perceptions towards Mid Valley Megamall's servicescapes in 2008 / Nur Fazliana Mohd Zuki - Mohd ZukiNur Fazliana Mohd Zuki, Nur Fazliana (Faculty of Business and Management, 2008)
This research is conducted for the purposed of "Customers' Perceptions towards Mid Valley Megamall's Servicescapes in 2008". With the fast growing numbers of shopping malls and giant shopping malls (megamall) around the world and Malaysia principally, the competitions for these companies to be the best attraction for the customers are very stiffs. This is because the attraction can lead for bigger crowds and in the greatest extent; the shopping mall can be one of the tourists' attractions for shopping in one country. Since these facilities are only a service provider, their services are usually be assessed by their service environment or the servicescapes of their facilities. This research is particularly to study customers' perceptions towards the servicescapes in terms of the location of the facility, the interior and exterior design, the ambient condition and interpersonal condition. The main objectives of the research are to measure the level of customers' perceptions towards servicescapes of Mid Valley Megamall, to recognize the relationship between respondents' demographic profiles with customers' perceptions towards servicescapes of Mid Valley Megamall and to identify the relationship between the servicescapes and customers' perceptions towards Mid Valley Megamall. This research is conducted by using non-probability sampling technique and the sampling method used is quota sampling. 100 customers of Mid Valley Megamall were selected to be the respondents by distributing each of them a questionnaire to answer. The conclusions of the study were from the outcome from the data analysis and findings. Based on the findings, some of the recommendations are suggested for the benefit of future research.